STRATEGI PENDIDIKAN NON FORMAL DALAM MEMBANGUN PERUBAHAN SOSIAL DI DESA HEGARMANAH KECAMATAN PANGGARANGAN KABUPTEN LEBAK - Ganiadi, Mochamad (Jurnal Pengabdian Dinamika, 2022)
This research method used qualitative with a case study approach. in this study in collection datawas carried out by means of observation, document study, in-depth interviews. The results of thisstudy indicate that the Non-Formal Education Strategies in building social change in the Village ofHegarmanah, Panggarangan sub district, Lebak District, has successfully implemented a strategyNonformal Education. The implementation strategy is carried out on the development of financing,facilities and infrastructure, as well as the quality of graduates and society achievement. Theresults of the study analysis implementation in the position of Strengths Opportunities, by using thestrengths of educational nonformalinstitutions. The results analysis that produce implementationnonformal education strategies,are a people understanding and feel the importance of insultingstunting (b) people realize the importance of maintaining a clean environment (c) people realize theimportance of managing waste, (d) the community realizes the importance of building a villageeconomic business, (e) people realize the importance of having education. While the results ofresearchontheimplementationofthestagesaccordingtothetheoryCommunicationOfInnovations Everett M. Rogers and F Floyd Shoemaker.